Integrasi Penggunaan Perangkat Puitis Berbasis Web Sebagai Media Pembelajaran Menulis Kreatif Puisi Berbahasa Inggris - Rizal, Sarif Syamsu (TRANSFORMATIKA, 2024)
The impact of advances in technology and information, one viral phenomenon "Liberating Learning Styles and Talent Interests of Learners" in this digital era, encourages the integration of various information technology applications in the learning process. One of them is using daring learning tools in the education process. Therefore, this research is entitled "Integration of the Use of Web-Based Poetic Devices as a Learning Media for Creative Writing of English Poetry" This research method is Research and Development is used to find a Model of Creative Writing of English Poetry Using Web-Based Poetic Devices and Simulations. The research results in the form of scientific knowledge concepts about poetry and poetry writing, introduction and application of the use of web-based daring poetic tools, models, methods, and steps of web-based daring poetic tools in poetry writing, and simulations of writing English poetry are four findings that will be discussed in detail in the discussion. The discussion in the study consists of Scientific Concepts of Poetry and Poetry Writing, Introduction and Application of the Use of Web-Based Daring Poetic Device Tools, Models, Methods, and Steps of Using Web-Based Poetic Device Tools, and Simulation of Writing English Poetry Using Web-Based Poetic Device Tools.